1989
DOI: 10.1111/j.1476-5381.1989.tb16876.x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin induces an increase in renal vascular resistance and a fall in glomerular filtration rate in the rabbit isolated perfused kidney

Abstract: 1 The effects of endothelin infusion on renal vascular resistance (RVR), glomerular filtration rate (GFR) and the interaction with locally generated endothelium-derived relaxant factor (EDRF) were studied in the rabbit isolated perfused kidney (IPK). For comparison the effects of infusions of angiotensin II (All) and noradrenaline (NA) were also assessed. 2 Each kidney was perfused at a constant rate of 1Oml minm and alterations in RVR determined by measuring changes in perfusion pressure. GFR was determined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Cairns et al reported the possibility that ET-1 at a pressor dose reduced the GFR by vasoconstriction of the afferent glomerular vessels in the rabbit PK [10]. We also observed a large increase in perfusion pressure with a reduction in the GFR following infusion of a high dose of ET-3, suggesting contraction of the renal arteries.…”
Section: Discussionsupporting
confidence: 63%
“…Cairns et al reported the possibility that ET-1 at a pressor dose reduced the GFR by vasoconstriction of the afferent glomerular vessels in the rabbit PK [10]. We also observed a large increase in perfusion pressure with a reduction in the GFR following infusion of a high dose of ET-3, suggesting contraction of the renal arteries.…”
Section: Discussionsupporting
confidence: 63%
“…Intrarenal infusion of ET-1 decreases renal blood flow and glomerular filtration rate while increasing sodium excretion. 3,7,8 Previous studies have demonstrated that ET-1 constricts the afferent arteriole 9 -13 ; however, the preglomerular vascular smooth muscle cellular signaling mechanisms responsible are not well understood. ET-1 activates G proteins that in turn stimulate phospholipase C and subsequent release of intracellular calcium ions ([Ca 2ϩ ] i ), leading to vascular smooth muscle cell contraction.…”
mentioning
confidence: 99%
“…The systemic vasodila tor response to ET-1 in rats is blocked by previous administration of nitric oxide synthetase inhibitors (7). ET-1 increases renal vascular resistance in the isolated perfused rabbit kidney (IPK); and at this level, its action is only slightly increased by inhibitors of endothelium-derived relaxing factor, methylene blue and hemoglobin (8).…”
mentioning
confidence: 99%